Towards Elucidating the Rotary Mechanism of the Archaellum Machinery - Nuno de Sousa Machado, João; Albers, Sonja-Verena; Daum, Bertram (Frontiers in Microbiology, 2022)
Motile archaea swim by means of a molecular machine called the archaellum. This structure consists of a filament attached to a membrane-embedded motor. The archaellum is found exclusively in members of the archaeal domain, but the core of its motor shares homology with the motor of type IV pili (T4P). Here, we provide an overview of the different components of the archaellum machinery and hypothetical models to explain how rotary motion of the filament is powered by the archaellum motor.